Application of high-selectivity catalyst Cu-ZnO / TiO2-P25 in synthesis of benzimidazole in heterogeneous system

By using Cu-ZnO/TiO2 catalyst in a heterogeneous system, catalyzing the reaction of ortho-phenylenediamine with CO2 and H2 to synthesize benzimidazole, the limitations of precious metal catalysts in the prior art are solved, and the green synthesis effect with high selectivity and high conversion is achieved.

CN119707827AActive Publication Date: 2025-03-28ANHUI UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510035897.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-28
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The prior art has limitations in the use of precious metal catalysts in the green synthesis of benzimidazoles, and there is a lack of a simple, green non-precious metal-based catalyst synthesis route.

Method used

Cu-ZnO/TiO2 is used as a highly selective catalyst to react ortho-phenylenediamine with CO2 and H2 in a heterogeneous system to synthesize benzimidazole. The catalyst is prepared by deposition-precipitation method, and P25-type TiO2 is used as a support to reduce raw material costs and improve catalytic efficiency.

Benefits of technology

The synthesis of benzimidazole with high selectivity (selectivity greater than 99.9%) and high conversion (conversion rate is 100%) is achieved. The preparation method of the catalyst is low in cost and has industrial prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707827A_ABST
    Figure CN119707827A_ABST
Patent Text Reader

Abstract

The invention relates to application of a high-selectivity catalyst Cu-ZnO / TiO2 in synthesis of benzimidazole in a heterogeneous system, and belongs to the technical field of catalyst preparation and application. According to the catalyst, zinc nitrate hexahydrate serves as a zinc source, copper nitrate trihydrate serves as a copper source, P25 type titanium dioxide serves as a carrier, ZnO and Cu are loaded on titanium dioxide through a fractional precipitation method, the titanium dioxide is put into a tubular furnace for hydrogen reduction, the catalyst Cu-ZnO / TiO2 is obtained, then CO2 serves as a carbon source, hydrogen serves as a hydrogen source, o-phenylenediamine is catalyzed to react, and benzimidazole is synthesized. The Cu-ZnO / TiO2 catalyst with the content of copper being 5% and the content of zinc oxide being 4% has excellent catalytic performance, and under the reaction conditions that the CO2 pressure is 2.5 MPa, the hydrogen pressure is 3.5 MPa and the temperature is 180 DEG C, when the conversion rate of o-phenylenediamine is 100%, the selectivity of benzimidazole is larger than 99.9%, and the TOF value is 6.4 h <-1 >. The preparation method is simple and low in cost, is used for catalyzing o-phenylenediamine to react with CO2 and H2 to prepare benzimidazole, is high in selectivity and has a wide industrialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of non-precious metal catalysts, and specifically relates to a highly selective catalyst Cu-ZnO / TiO 2 Catalytic reaction of o-phenylenediamine with CO in a heterogeneous system 2、 H 2 Application of the reaction in the synthesis of benzimidazoles. Background Art

[0002] Benzimidazole, molecular formula C 7 H 6 N 2 It is a colorless flaky crystal with a relative molecular weight of 118.14, a melting point of 171°C, a boiling point of 360°C, slightly soluble in water and ether, and easily soluble in ethanol, acid solution, and strong alkaline solution. Benzimidazole can be used to prepare intermediate imidazoles such as fungicides such as imazalil and prochloraz, and can also be used to synthesize drugs such as vitamin B12 and prepare polymer compounds. It is usually synthesized by cyclization of o-phenylenediamine and formic acid. Although great progress has been made in the synthesis of benzimidazole, from the perspective of green chemistry and sustainable development, the use of non-precious metal catalysts to develop simple and green synthetic routes is still a problem worthy of attention.

[0003] O-phenylenediamine is easily oxidized by CO under relatively mild conditions. 2 The first report of the synthesis of benzimidazoles via this cyclization appeared in 2013 when Liu and colleagues used RuCl 2 (1,2-Bis(diphenylphosphino)ethane) 2 Catalyst, under solvent-free conditions, cyclization of o-phenylenediamine to benzimidazole. Hao et al. 2 In the presence of Au / TiO 2 Catalytic synthesis of cheap and readily available o-nitroaniline and CO 2 Other supported gold catalysts, such as Au / Al 2 O 3 and Au / polyurea were also found to promote the reaction, albeit with reduced efficiency. Saptal et al. designed polymer ionic liquid-supported ruthenium nanoparticles (Ru@PsIL) as CO 2 A novel catalyst for the catalytic immobilization of azole compounds in Ru@PsIL and K 2 CO 3 Under the dual catalysis of CO and NH4+, o-phenylenediamine or o-nitroaniline can be used as raw materials to produce 2 and DMAB to synthesize azole compounds. Khatun et al. implanted copper nanoparticles into covalent organic frameworks to design CO 2The catalyst for synthesizing azole compounds successfully prepared CuNPs@COF with Cu nanoparticles confined in the pores of COF materials and used for the synthesis of benzimidazole, benzothiazole and benzoxazole derivatives. Compared with other heterogeneous catalyst systems, the developed CuNPs@COF catalyst can convert different aromatic amine reagents into corresponding products in a shorter reaction time. As can be seen from the above examples, although great progress has been made in the synthesis of benzimidazole, the development of simple, efficient and green non-precious metal-based catalysts is still an important research direction.

[0004] In conclusion, the development of new non-precious metal-based catalysts for efficient catalysis of CO 2 The reaction of benzoimidazole with o-phenylenediamine to prepare benzimidazole is of great significance. Summary of the invention

[0005] In view of the above problems existing in the existing catalytic synthesis of benzimidazole technology, the present invention aims to provide a highly selective catalyst Cu-ZnO / TiO 2 Catalytic reaction of o-phenylenediamine with CO in a heterogeneous system 2 , H 2 The application of synthesizing benzimidazole, the catalyst preparation method has low cost, high catalytic application conversion rate, high selectivity of target product, and has industrialization prospects.

[0006] To achieve the above purpose, the present invention adopts the following technical solutions.

[0007] The purpose of the present invention is to provide a highly selective catalyst Cu-ZnO / TiO 2 Application of the synthesis of benzimidazoles in heterogeneous systems, based on Cu-ZnO / TiO 2 As catalyst, N-methylpyrrolidone is used as solvent, and added to o-phenylenediamine and CO 2 , H 2 In the reaction system, o-phenylenediamine is catalyzed to react with CO 2 , H 2 The reaction generates benzimidazole, and the catalytic reaction formula is as follows:

[0008] Preferably, in CO 2 Under the reaction conditions of 2.5 MPa pressure, 3.5 MPa hydrogen pressure and 180 °C, when the conversion rate of o-phenylenediamine was 100%, the selectivity of benzimidazole was greater than 99.9% and the TOF value was 6.4 h -1 .

[0009] Preferably, the catalyst Cu-ZnO / TiO 2 , Cu and ZnO are loaded on P25 TiO 2In general, the loading amount of Cu is 1-9 wt% of the catalyst, and the loading amount of ZnO is 2-8 wt% of the catalyst.

[0010] Preferably, the loading amount of Cu is 5 wt% of the catalyst and the loading amount of ZnO is 4 wt% of the catalyst.

[0011] In Cu-ZnO / TiO 2 The method of expressing the loading amount of Cu and ZnO in the catalyst is directly abbreviated as 1-9% and 2-8% in the subsequent content of this article, and its meaning is the same as the 1-9 wt% and 2-8 wt% recorded in this article.

[0012] The above catalyst Cu-ZnO / TiO 2 The preparation steps are as follows: (1) P25 TiO 2 Add zinc nitrate hexahydrate to pure water and stir evenly. Put the obtained suspension into a water bath at 60-80 °C, stir vigorously, and add the precipitant -Na drop by drop. 2 CO 3 The solution was adjusted to pH 10-12, the mixture was stirred for 0.5 h, the precipitate was collected, washed until the pH value was 7, the sample was dried in a vacuum oven at 60 °C for 12 h, and calcined in a muffle furnace in an air atmosphere to obtain ZnO / TiO 2 Carrier; (2) ZnO / TiO 2 The carrier and copper nitrate trihydrate were added to pure water and stirred evenly. The resulting suspension was placed in a 50-70 ℃ water bath, stirred vigorously, and the precipitant -Na was added dropwise. 2 CO 3 The solution was adjusted to pH 8-10, and the resulting mixture was stirred for 2 h. The precipitate was collected, washed until the pH value was 7, and then dried in a vacuum oven at 60 °C for 12 h to obtain unreduced Cu-ZnO / TiO 2 ; (3) The unreduced catalyst Cu-ZnO / TiO 2 , put it into a tube furnace, heat and reduce it in a hydrogen atmosphere, and cool it naturally to room temperature to obtain Cu-ZnO / TiO 2 .

[0013] In the above preparation method, zinc nitrate hexahydrate in step (1) may also be replaced by zinc sulfate or zinc chloride, and copper nitrate trihydrate in step (2) may also be replaced by copper sulfate or copper chloride, and the technical effects produced are the same.

[0014] Preferably, in step (1), the P25 type TiO 2The molar ratio of zinc nitrate hexahydrate is 3-14:1.

[0015] Preferably, in step (1), the heating rate of the muffle furnace is 5°C / min, the calcination temperature is 250-450°C, and the calcination time is 3.5-4.5 h. Since the calcination of the carrier is to obtain a carrier with a rich pore structure, the calcination temperature and time are reasonably controlled to maintain the carrier with a stable structure.

[0016] Preferably, in step (2), ZnO / TiO 2 The mass ratio of the carrier to the copper nitrate trihydrate is 2-26:1.

[0017] Preferably, in step (1) and step (2), Na 2 CO 3 The concentration of the solutions was 0.1 g / mL.

[0018] Preferably, in step (2), the heating rate of the tubular furnace is 5°C / min, the reduction temperature in the tubular furnace is 200-400°C, and the reduction time is 1-3 h.

[0019] Highly selective catalyst Cu-ZnO / TiO 2 The specific steps for synthesizing benzimidazole in a heterogeneous system are as follows: (1) Select a stainless steel high-pressure reactor and insert a glass container as the reactor lining; (2) Weigh the catalyst Cu-ZnO / TiO 2 In a high-pressure reactor, weigh o-phenylenediamine and dissolve it in N-methylpyrrolidone solvent, and after ultrasonic dispersion, place the mixed solution in the high-pressure reactor; (3) After sealing the reactor, evacuate it three times with hydrogen at a pressure of 1 MPa, maintain the hydrogen pressure at 1 MPa at room temperature, and check the airtightness of the reactor; (4) First heat the reactor to 180°C, continue to introduce hydrogen to 3.5 MPa, then introduce carbon dioxide to 6 MPa, maintain the temperature and pressure in the reactor and react for 1 hour; (5) After the reaction is completed and cooled to room temperature, open the gas valve of the high-pressure reactor and release the gas in the reactor until the pressure reaches 0, completing the reaction process.

[0020] Compared with the prior art, the present invention has the following beneficial effects: The catalyst Cu-ZnO / TiO of the present invention 2 Prepared by deposition-precipitation method, with non-precious metal as active phase, P25 type TiO 2As a carrier, it greatly reduces the cost of raw materials, and the preparation method is simple, green and environmentally friendly, and has industrial prospects; The 5%Cu-4%ZnO / P25 catalyst prepared by the present invention has excellent catalytic performance; 2 Under the reaction conditions of pressure 2.5 MPa, hydrogen pressure 3.5 MPa, temperature 180 ℃, reaction 0.25 h, and catalyst 100 mg, when the conversion rate of 0.108 g of o-phenylenediamine was 100%, the selectivity of benzimidazole was greater than 99.9%. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The Cu-ZnO / TiO prepared in Example 3 2 XRD patterns of the catalysts.

[0022] Figure 2 The Cu-ZnO / TiO prepared in Example 3 2 Time course diagram of catalyst.

[0023] Figure 3 The Cu-ZnO / TiO prepared in Example 3 2 Catalyst stability experimental performance diagram.

[0024] Figure 4 The Cu-ZnO / TiO prepared in Example 3 2 TEM image of the catalyst. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is further described below with reference to specific embodiments, but the protection scope of the present invention is not limited thereto.

[0026] In the present invention, Cu and ZnO are loaded on P25 type TiO 2 Preparation of Cu-ZnO / TiO 2 For example, to detect the performance and parameters of the product and determine the optimal performance of the product.

[0027] In the following specific examples 1-8, the catalyst was prepared using the following steps: (1) P25 TiO 2 Add zinc nitrate hexahydrate to pure water and stir evenly. Put the obtained suspension into a 70 ℃ water bath, stir vigorously, and add 0.1 g / mL precipitant -Na 2 CO 3The solution was adjusted to pH 11, and the obtained mixture was stirred for 0.5 h. The formed precipitate was collected and washed to pH 7. The obtained sample was placed in a vacuum drying oven at 60 °C for 12 h and calcined in a muffle furnace in an air atmosphere. The muffle furnace was heated to 350 °C at a heating rate of 5 °C / min and the calcination time was 3 h to obtain ZnO / TiO 2 Carrier; (2) ZnO / TiO 2 The carrier and copper nitrate trihydrate were added to pure water and stirred evenly. The resulting suspension was placed in a 60 °C water bath and stirred vigorously. The precipitant -Na with a concentration of 0.1 g / mL was added dropwise. 2 CO 3 The solution was adjusted to pH 9, and the resulting mixture was stirred for 2 h. The precipitate was collected, washed until the pH value was 7, and then dried in a vacuum oven at 60 °C for 12 h to obtain unreduced Cu-ZnO / TiO 2 ; (3) The unreduced catalyst Cu-ZnO / TiO 2 , put it into a tube furnace, and heat it for 2 h in a hydrogen atmosphere, heating it to 300 °C at a heating rate of 5 °C / min, reducing it for 2 h, and cooling it naturally to room temperature to obtain Cu-ZnO / TiO 2 .

[0028] Among them, in the amount of raw materials, by controlling the P25 type TiO 2 The molar ratio of ZnO / TiO to zinc nitrate hexahydrate is 3-14:1, and 2 The mass ratio of the carrier to copper nitrate trihydrate is 2-26:1, and Cu and ZnO can be loaded in the catalyst in different proportions.

[0029] The application test of the catalyst prepared by the above method for catalytic synthesis of benzimidazole is as follows: it is carried out in a 200 mL stainless steel autoclave, and a glass container is inserted as the lining of the autoclave; 100 mg of the catalyst is weighed into the autoclave, and then 0.108 g of o-phenylenediamine and 20 mL of N-methylpyrrolidone are weighed, and o-phenylenediamine is dissolved in N-methylpyrrolidone, and the mixed solution is placed in the autoclave after ultrasonic dispersion. After sealing the reactor, it is evacuated three times with hydrogen (1 MPa), and the hydrogen pressure is increased by 1 MPa at room temperature, and the airtightness is checked. After checking the airtightness, the magnetic speed is adjusted to 550 rpm, and when the temperature of the autoclave is raised to 180 °C, hydrogen is introduced until the pressure reaches 3.5 MPa, and then CO is introduced. 2 When the pressure reaches 6 MPa, start timing. After 1 h of reaction, cool to room temperature, open the gas valve of the autoclave and release the gas in the autoclave until the pressure reaches 0 MPa.

[0030] After filtering the reaction solution, 0.4 μL was drawn with a micro-injection needle and injected into the gas chromatograph. The gas chromatograph hydrogen flow rate was set to 40~60 mL / min, the air flow rate was 200~300 mL / min, and the carrier gas flow rate was 2~3 mL / min. The injection temperature was set to 280.0 ℃, the initial temperature of the column furnace was set to 150 ℃ and maintained for 10 min, then heated to 280 ℃ at 25 ℃ / min and maintained for 10 min, and the FID temperature was set to 280.0 ℃. Using n-dodecane as the internal standard, the conversion rate and selectivity of the catalysts of different embodiments for synthesizing benzimidazole from o-phenylenediamine were calculated by gas chromatography.

[0031] Example 1: 5%Cu-2%ZnO / TiO 2 Catalytic synthesis of benzimidazole from o-phenylenediamine The catalyst of Example 1 of the present invention catalyzes the reaction of o-phenylenediamine with CO 2 , H 2 The performance test conditions and results of synthetic benzimidazole application test are as follows: At a hydrogen pressure of 3.5 MPa, CO 2 Under the reaction conditions of pressure 2.5 MPa, temperature 180 ℃, reaction time 0.25 h, catalyst 100 mg, and o-phenylenediamine 0.108 g, the catalyst conversion rate was 18.7% and the selectivity of benzimidazole was greater than 99.9%.

[0032] Example 2: 5%Cu-4%ZnO / TiO 2 Catalytic synthesis of benzimidazole from o-phenylenediamine The catalyst of Example 2 of the present invention catalyzes the reaction of o-phenylenediamine with CO 2 , H 2 The performance test conditions and results of synthetic benzimidazole application test are as follows: At a hydrogen pressure of 3.5 MPa, CO 2 Under the reaction conditions of pressure 2.5 MPa, temperature 180 ℃, reaction time 0.25 h, catalyst 100 mg, and o-phenylenediamine 0.108 g, the catalyst conversion rate was 34.1% and the selectivity of benzimidazole was greater than 99.9%.

[0033] Example 3: 5%Cu-6%ZnO / TiO 2 Catalytic synthesis of benzimidazole from o-phenylenediamine The catalyst of Example 3 of the present invention catalyzes the reaction of o-phenylenediamine with CO 2 , H 2 The performance test conditions and results of synthetic benzimidazole application test are as follows: Under the reaction conditions of hydrogen pressure of 3.5 MPa, carbon dioxide pressure of 2.5 MPa, temperature of 180 ℃, reaction time of 0.25 h, catalyst of 100 mg, and o-phenylenediamine of 0.108 g, the catalyst conversion rate was 23.8% and the selectivity of benzimidazole was greater than 99.9%.

[0034] Example 4: 5%Cu-8%ZnO / TiO 2 Catalytic synthesis of benzimidazole from o-phenylenediamine The catalyst of Example 4 of the present invention catalyzes the reaction of o-phenylenediamine with CO 2 , H 2 The performance test conditions and results of the synthetic benzimidazole application test are as follows: Under the reaction conditions of hydrogen pressure of 3.5 MPa, carbon dioxide pressure of 2.5 MPa, temperature of 180 ℃, reaction time of 0.25 h, catalyst of 100 mg, and o-phenylenediamine of 0.108 g, the catalyst conversion rate was 15.1% and the selectivity of benzimidazole was greater than 99.9%.

[0035] Comparative Example 1: Synthesis of benzimidazole from o-phenylenediamine catalyzed by 5% Cu / ZnO The 5% Cu / ZnO in Comparative Example 1 was used to catalyze the synthesis of benzimidazole from phenylenediamine, and the performance test conditions and results were as follows: Under the reaction conditions of hydrogen pressure of 3.5 MPa, carbon dioxide pressure of 2.5 MPa, temperature of 180 ℃, reaction time of 0.25 h, catalyst of 100 mg, and o-phenylenediamine of 0.108 g, the catalyst conversion rate was 0.8% and the selectivity of benzimidazole was greater than 99.9%.

[0036] Comparative Example 2: 5%Cu / TiO 2 Catalytic synthesis of benzimidazole from o-phenylenediamine The 5% Cu / TiO 2 The catalytic synthesis of benzimidazole by phenylenediamine was tested, and the performance test conditions and results are as follows: Under the reaction conditions of hydrogen pressure of 3.5 MPa, carbon dioxide pressure of 2.5 MPa, temperature of 180 ℃, reaction time of 0.25 h, catalyst of 100 mg, and o-phenylenediamine of 0.108 g, the catalyst conversion rate was 9.1% and the selectivity of benzimidazole was greater than 99.9%.

[0037] Example 5: 1%Cu-4%ZnO / TiO 2 Catalytic synthesis of benzimidazole from o-phenylenediamine The catalyst of Example 5 of the present invention catalyzes the reaction of o-phenylenediamine with CO 2 , H 2The performance test conditions and results of the synthetic benzimidazole application test are as follows: Under the reaction conditions of hydrogen pressure of 3.5 MPa, carbon dioxide pressure of 2.5 MPa, temperature of 180 ℃, reaction time of 0.25 h, catalyst of 50 mg, and aniline of 0.1 g, the catalyst conversion rate was 11.7% and the selectivity of benzimidazole was greater than 99.9%.

[0038] Example 6: 9%Cu-4%ZnO / TiO 2 Catalytic synthesis of benzimidazole from o-phenylenediamine The catalyst of Example 6 of the present invention catalyzes the reaction of o-phenylenediamine with CO 2 , H 2 The performance test conditions and results of the synthetic benzimidazole application test are as follows: Under the reaction conditions of hydrogen pressure of 3.5 MPa, carbon dioxide pressure of 2.5 MPa, temperature of 180 ℃, reaction time of 0.25 h, catalyst of 100 mg, and o-phenylenediamine of 0.108 g, the catalyst conversion rate was 19.7% and the selectivity of benzimidazole was greater than 99.9%.

[0039] Example 7: 5%Cu-4%ZnO / TiO 2 Catalytic synthesis of benzimidazole from o-phenylenediamine The catalyst of Example 7 of the present invention is prepared by reducing the hydrogen at a temperature of 200°C, and then catalyzing the reaction of o-phenylenediamine with CO 2 , H 2 The performance test conditions and results of the synthetic benzimidazole application test are as follows: Under the reaction conditions of hydrogen pressure of 3.5 MPa, carbon dioxide pressure of 2.5 MPa, temperature of 180 ℃, reaction time of 0.25 h, catalyst of 100 mg, and o-phenylenediamine of 0.108 g, the catalyst conversion rate was 28.3% and the selectivity of benzimidazole was greater than 99.9%.

[0040] Example 8: 5%Cu-4%ZnO / TiO 2 Catalytic synthesis of benzimidazole from o-phenylenediamine The catalyst of Example 8 of the present invention is prepared by reducing the hydrogen at a temperature of 400°C, and then catalyzing the reaction of o-phenylenediamine with CO 2 , H 2 The performance test conditions and results of the synthetic benzimidazole application test are as follows: Under the reaction conditions of hydrogen pressure of 3.5 MPa, carbon dioxide pressure of 2.5 MPa, temperature of 180 ℃, reaction time of 0.25 h, catalyst of 100 mg, and o-phenylenediamine of 0.108 g, the catalyst conversion rate was 31.8% and the selectivity of benzimidazole was greater than 99.9%.

[0041] The catalyst prepared in Implementation 2 was subjected to a spectrum test, an electron microscope scan, a catalytic activity test, and a stability test, and the test results are as follows.

[0042] Figure 1 Figure 2 is the XRD pattern of the catalyst prepared in Example 2 before and after the catalytic reaction. It can be observed that P25 type TiO 2 The characteristic peaks of ZnO (100), (002), (101) crystal planes and Cu (111) crystal planes can be observed in the spectrum. The XRD pattern of the catalyst prepared in Example 2 before and after the catalytic reaction is almost unchanged. The size of the Cu particles in the catalyst before and after the reaction is 5 nm, indicating that the catalyst has a stable structure and is a recyclable multiphase catalyst.

[0043] Figure 2 This is a Time course diagram of the catalyst prepared in Example 3. It can be seen from the figure that when the reaction time is 0 h, 0.25 h, 0.5 h, 1 h, 2 h, 4 h, 6 h and 7 h, the conversion rate of o-phenylenediamine is 22.5%, 34.1%, 47.5%, 58.1%, 72.3%, 88.7%, 98.7% and 100.0%, respectively, and the selectivity of benzimidazole is maintained at more than 99.9%. It can be concluded that the catalyst prepared in Example 2 has high catalytic activity and selectivity.

[0044] Figure 3 The stability experimental performance diagram of the catalyst prepared in Example 3 shows that when the catalyst is cycled for the first, second, third and fourth times, the conversion rates of aniline are 34.1%, 34.9%, 34.1% and 34.0%, respectively, and the selectivity of benzimidazole is greater than 99.9%. It can be concluded that the catalyst has high stability.

[0045] Figure 4 This is a TEM image of the catalyst prepared in Example 3. It can be seen from the figure that Cu and ZnO are loaded on the P25 type TiO 2 The Cu particle size is 5 nm.

[0046] The catalytic performance of the catalyst products obtained under different conditions on aniline under the same reaction conditions is shown in Table 1.

[0047] Table 1: Effect of different loading amounts on catalytic activity

[0048] It can be seen from Examples 1 to 4 in Table 1 that the loading amount of ZnO has a great influence on the catalyst activity. When the loading amount content is from 2% to 8%, the conversion selectivity of o-phenylenediamine first increases and then decreases, and the benzimidazole selectivity is greater than 99.9%, which means that the catalytic performance of the catalyst also increases first and then decreases, showing a volcano-shaped trend. When the loading amount is 4%, the conversion rate reaches a maximum of 34.1% and the selectivity is greater than 99.9%.

[0049] It can be seen from Example 2, Example 5, and Example 6 that the Cu loading still has a great influence on the catalyst activity. When the loading amount is from 1% to 9%, the conversion selectivity of o-phenylenediamine first increases and then decreases, and the benzimidazole selectivity is greater than 99.9%. When the loading amount is 5%, the conversion rate reaches a maximum of 34.1% and the selectivity is greater than 99.9%.

[0050] It can be seen from Example 2, Comparative Example 1 and Comparative Example 2 that ZnO and Cu have a synergistic effect on the catalytic performance of the catalyst, and can significantly improve the catalytic performance of the catalyst.

[0051] It can be seen from Example 2, Example 7, and Example 8 that the reduction temperature of hydrogen also has a great influence on the performance of the catalyst. As the reduction temperature increases from 200°C to 400°C, the catalytic performance of the catalyst first increases and then decreases. When the reduction temperature is 300°C, the catalytic performance of the catalyst reaches the highest.

[0052] The above description is only part of the embodiments of the present invention and is not intended to limit the present invention. All equivalent changes and modifications made according to the content of the present invention are within the protection scope of the present invention.

Claims

1. An application of a highly selective catalyst Cu-ZnO / TiO2 in the synthesis of benzimidazole in a heterogeneous system, characterized in that: Cu-ZnO / TiO2 is used as a catalyst and N-methylpyrrolidone is used as a solvent. It is added into the reaction system of o-phenylenediamine, CO2 and H2 to catalyze the reaction of o-phenylenediamine with CO2 and H2 to generate benzimidazole.

2. The use according to claim 1, characterized in that: Under the reaction conditions of CO2 pressure of 2.5 MPa, hydrogen pressure of 3.5 MPa and temperature of 180 ℃, when the conversion rate of o-phenylenediamine was 100%, the selectivity of benzimidazole was greater than 99.9% and the TOF value was 6.4 h -1 .

3. The use according to claim 1 or 2, characterized in that: The catalyst Cu-ZnO / TiO2, Cu and ZnO are loaded on P25 type TiO2, the Cu loading is 1-9 wt% of the catalyst, and the ZnO loading is 2-8 wt% of the catalyst.

4. The use according to claim 3, characterized in that: The Cu loading was 5 wt% of the catalyst, and the ZnO loading was 4 wt% of the catalyst.

5. The use according to claim 3, characterized in that: The preparation steps of the catalyst Cu-ZnO / TiO2 are as follows: (1) P25 TiO2 and zinc nitrate hexahydrate were added to pure water and stirred evenly. The obtained suspension was placed in a water bath at 60-80 °C and stirred vigorously. A precipitant - Na2CO3 solution was added dropwise to adjust the pH to 10-12. The obtained mixture was stirred for 0.5 h. The formed precipitate was collected and washed to a pH of 7. The obtained sample was placed in a vacuum drying oven at 60 °C and dried for 12 h. It was then calcined in a muffle furnace in an air atmosphere to obtain a ZnO / TiO2 carrier. (2) Add ZnO / TiO2 carrier and copper nitrate trihydrate into pure water and stir evenly. Place the obtained suspension in a water bath at 50-70°C and stir vigorously. Add precipitant-Na2CO3 solution dropwise to adjust the pH to 8-10. Continue stirring the obtained mixture for 2 h. Collect the formed precipitate, wash it to pH 7, and then dry it in a vacuum drying oven at 60°C for 12 h to obtain unreduced Cu-ZnO / TiO2. (3) The unreduced catalyst Cu-ZnO / TiO2 is placed in a tubular furnace, heated and reduced under a hydrogen atmosphere, and naturally cooled to room temperature to obtain Cu-ZnO / TiO2.

6. The use according to claim 5, characterized in that: In the preparation step (1) of the high-selectivity catalyst Cu-ZnO / TiO2, the mass ratio of P25-type TiO2 to zinc nitrate hexahydrate is 3-14:

1.

7. The use according to claim 5, characterized in that: In the preparation step (1) of the highly selective catalyst Cu-ZnO / TiO2, the heating rate of the muffle furnace is 5°C / min, the calcination temperature is 250-450°C, and the calcination time is 3.5-4.5 h.

8. The use according to claim 5, characterized in that: In the preparation step (2) of the high-selectivity catalyst Cu-ZnO / TiO2, the mass ratio of the ZnO / TiO2-P25 carrier to copper nitrate trihydrate is 2-26:

1.

9. The use according to claim 5, characterized in that: In the preparation steps (1) and (2) of the highly selective catalyst Cu-ZnO / TiO2, the concentration of the Na2CO3 solution is 0.1 g / mL.

10. The use according to claim 3, characterized in that: In the preparation step (3) of the highly selective catalyst Cu-ZnO / TiO2, the heating rate of the tubular furnace is 5°C / min, the reduction temperature in the tubular furnace is 200-400°C, and the reduction time is 1-3h.

Citation Information

Patent Citations

  • Method for synthesizing benzimidazole compound

    CN102863389A

  • Method for synthesizing benzimidazole compounds

    CN103288743A

  • Method for preparing benzimidazole compound through supported bimetallic catalyst at room temperature

    CN105837512A

  • Method for synthesizing benzimidazole compound through copper catalysis

    CN111057010A

  • Method for synthesizing 2-substituted benzimidazole under catalysis of nano copper-zinc alloy

    CN117263868A